2010
DOI: 10.1021/ac101021q
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Size Discrimination of Gold Nanoparticles Attached to Glass/Indium−Tin-Oxide Electrodes by Oxidation in Bromide-Containing Electrolyte

Abstract: Here we describe the electrochemical oxidation of an assembly of gold nanoparticles (Au NPs) attached to glass/indium-tin-oxide (ITO) electrodes as a function of particle size. We synthesized Au NP arrays with NP diameters ranging from 8 to 250 nm by electrodeposition of Au from HAuCl(4) in H(2)SO(4) at potentials of -0.2 to 0.8 V versus Ag/AgCl using chronocoulometry to keep the amount of Au deposited constant. The average Au NP size increased with increasing deposition potential. The chemical reduction of HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
160
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(187 citation statements)
references
References 78 publications
27
160
0
Order By: Relevance
“…Figure 3 : experimental of peak potentials for the system (solid points) described in ref. [22]. The solid curve is calculated from eq.26.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3 : experimental of peak potentials for the system (solid points) described in ref. [22]. The solid curve is calculated from eq.26.…”
Section: Resultsmentioning
confidence: 99%
“…The second study by the same authors, reported here, considers gold nanoparticles [22]. In this paper, the authors describe the electrochemical oxidation of an assembly of gold nanoparticles (Au NPs) attached to glass/indium-tin-oxide (ITO) electrodes as a function of particle size.…”
Section: Fig1mentioning
confidence: 98%
See 1 more Smart Citation
“…53,246 The UV-Vis spectrometer is used to characterize the concentration of the AuNPs. The maximum absorption peak of the prepared AuNP was located at 504 nm ( Figure 16A).…”
Section: Characterization Of Citrate-capped Aunpsmentioning
confidence: 99%
“…34,35 In our group we were studying the effect of size dependence on the change of the Ep value. [36][37][38] It is very well know that in many cases the reactivity of metal nanoparticles is directly correlated to the decrease in size. A decrease in size changes the coordination number of the atoms at the surface of the nanoparticle.…”
Section: Importance Of Metal Nanoparticles Researchmentioning
confidence: 99%